THE ROLE OF STUDENTS IN COMMUNITY EMPOWERMENT THROUGH THE KKNT PROGRAM IN BABAKAN VILLAGE, CIREBON REGENCY - Lutvia Aulia Azzahra; Ghina Nur Afifah; Muhammad Rizky Firdaus; Fayed Alkadri Firdaus; H. Awliya Tribhuwana (Jurnal Abdisci, 2026)
Background. The Thematic Real Work Lecture activity in Babakan Village is motivated by the existence of problems in the health, education, and social aspects of the community that require education-based empowerment efforts. Aims. This research aims to determine the implementation and impact of the program on increasing public knowledge and awareness. Methods. The method used is a participatory approach through observation, socialization, education, and direct service to the community. The programs implemented include free health checks, stunting counseling and complementary feeding, youth social education, learning assistance, and technical activities such as the installation of road reflectors and village maps. Result. The results show that all programs can be implemented well and get a positive response and active participation from the community. Conclusion. This program is also able to increase public understanding of various health, education, and social issues. In conclusion, this activity is effective in supporting community empowerment through educational and participatory approaches. Implementation. The implications of this study show the importance of program sustainability and multi-stakeholder collaboration to achieve more optimal and sustainable impacts.